FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN AKTIVITAS FISIK PADA LANJUT USIA DI UPT PANTI SOSIAL TRESNAWERDHA KHUSNUL KHOTIMAH PEKANBARU - Efliani, Destria; Mayenti, Fitra (Jurnal Ilmu Keperawatan, 2023)
Physical activity is any body movement produced by skeletal muscles that requires sufficient energy or energy expenditure, if done excessively it will result in a person experiencing fatigue easily so that it will have an impact on the health of the elderly. The purpose of this study was to determine the factors associated with physical activity in the elderly at UPT Panti Sosial Elderly. This type of research is quantitative research design cross sectional. The population in this study totaled 32 respondents.  The sampling technique used in this study was nonprobability sampling with total sampling, data analysis using chi square test. The results of this study showed that the majority of respondents were 65.6%, the age of the respondents was in the elderly category, the sex of the majority was male 62.5%, and the eating pattern was lacking, the majority were 15 people, 46.9%, moderate physical activity was 59.4%. There is a relationship between age and physical activity (p value 0.001), there was no relationship between gender and physical activity (p value 0.114), there was a relationship between diet and physical activity (p value 0.002).  It is hoped that the elderly in the orphanage can increase physical activity such as elderly gymnastics, walking in the morning, doing home activities so that they can help increase the portion of food that is lacking and help improve a healthy lifestyle.